Knowledge and Attitudes Regarding Donated Milk and their Socio-demographic Predictors in Healthcare Providers in Tabriz, 2021: A Cross-sectional Study - Sima Golsanamloo; Mina Hosseinzadeh; Mojgan Mirghafourvand; Mohammadhassan Sahebihagh; Marjaneh Moein darbari Fooladi; Fariborz Roshangar (International Journal of Community Based Nursing and Midwifery, 2022)
Background: Donated milk is the best choice for infants who cannot receive breast milk from their mothers. Researchers in this study evaluated the knowledge and attitude of healthcare providers regarding milk-donation and examined their socio-demographic predictors in Tabriz-Iran, 2021.Methods: In this cross-sectional analytic study, the total sample size consisted of 535 healthcare providers including 272 nurses and midwives working at maternal hospitals and 263 healthcare providers working at healthcare-centers. Census-sampling method was used during October 2020 to February 2021, and data collection tools included socio-demographic, knowledge and attitude questionnaires. Pearson-correlation test, independent t-test, one-way analysis of variance, and adjusted general linear model were used to analyze the data using SPSS version 16.Results: The mean (SD) of the knowledge score was 12.04±4.30 (score range of 0-22) and that of the attitude score was 134.27±20.23 (score range of 42-210). Results of general linear model was adjusted for socio-demographic characteristics and showed that predictors of knowledge variable were associated with having prior experience of breastfeeding another infant (P=0.006) and encouraging others to breastfeed (P=0.008); also, the predictor of attitude variable was aligned with encouraging others to breastfeed (P<0.001).Conclusions: The findings of this study affirm that knowledge and attitude of healthcare providers were moderately influential for breast milk donation. Since they could play a responsible role in providing education, positive atmosphere for specialized training for the general public, the efforts to improve their knowledge and attitudes can contribute to acceptability of a milk-bank in the community and reduction of the rate of neonatal mortality in Iran.